POTRET IDEOLOGI PEMIKIRAN M SAID ASHMAWI TENTANG AYAT AHKAM DENGAN METODE KONTEKSTUAL - Bustami Saladin (UIN Mataram, 2018)
The term syarî’ah and several other terms that have the same root words in the Qur’an. He concluded that syarî’ah means tariq (road), sabil (path, method), and manhaj (method). Therefore, syarî’ah can be interpreted as a way or method of Allah or Islam. In this sense also includes the rules of law revealed in the Qur’an, then the rules contained in Hadith (verbal tradition), and then tafsir, opinion-opinions, and ijtihâd (personal opinion), fatwâ (religious opinion ulamâ, and judges’ decisions. In short, it encompasses all that complements and explains these fundamental rules for establishing Islamic jurisprudence (fiqh) as formed in history. Thus, in the Qur’an, it does not mean law (qânûn) or legislation (tashrf ), so that the issue of applying Islamic syarî’ah is nothing but a mere human invention